Innovation and transformation of ultrasound mechanicaleffects in medical theranostics - Zheng Hairong; Niu Lili; Wang Congzhi; Li Fei (生物医学转化, 2020)
At present, medical ultrasound technology is gradually developing from the traditional imagingof tissue and organ structure based on wave effect of ultrasound, and the treatment of diseased tissue based on thermal and cavitation effects, to the direction of multi-functional integration of diagnosis and treatment. Therefore, asone of the most important biological effects, the mechanical effect of ultrasound (i.e. acoustic radiation force) hasattracted more and more attention from scientific researchers and medical staffs. Benefiting from the in-depthunderstanding of the theory and mechanism of ultrasonic mechanical effect, as well as the rapid development ofinformation and electronic technology, a variety of new ultrasonic diagnosis and treatment technologies based onacoustic radiation force have emerged in recent years, which have greatly expanded the application of ultrasoundin clinics. For example, ultrasound elastography that can quantitatively measure the tissue stiffness and image itsdistribution, which can provide early screening for liver cirrhosis and breast cancer; as well as ultrasound neuromodulation that can non-invasively regulate the state of nerve cells in the brain, which can provide unique toolsfor brain disease treatment and neuroscience research. This article will systematically introduce the representativeachievements of these new medical ultrasound technologies based on the mechanical effect of ultrasound in recentyears, and analyze their future development directions.